Outlook of Diabetic Retinopathy Management through Universal Health Care in Indonesia from 2015 – 2020: Oral Presentation - Observational Study - Resident - Supanji; Zaharo, Alfia Fatma; Wardhana, Firman Setya; Sasongko, Muhammad Bayu (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesTo identify the National Health Expenditure associated with diabetic retinopathy (DR) from theperspective of Jaminan Kesehatan Nasional [JKN]. MethodsA dataset of 1% of all individuals registered in JKN database was used from 2015 to 2020. Weretrieved primary diagnosis with type 2 diabetes mellitus (T2DM) (ICD-10 E11) and/or T2DM withophthalmic complications (E11.3). Further diagnosis with DR (H36) was retrieved. Four groups ofmedical procedures related to DR management were developed according to Indonesian Case BaseGroups (INA-CBGs): diagnostic, laser photocoagulation and cryotherapy, minor (intravitrealinjection), and major surgical procedures (e.g., vitrectomy). We performed descriptive analyses forthe annual costs incurred for procedures, premium classifications, and regions. ResultsOverall DR costs were US $41.5 million from 156,752 individuals with DR in JKN database sample.The total cost and per unit procedures cost specifically increased annually from 2015 to 2019 butdeclined substantially in 2020. The largest amount was spent on intravitreal injection ($36.3 million[87.5%]), whereas vitrectomy was the least ($145.0 million [0.3%]). Region 1 (Java Island) with nonbeneficiariesof government subsidies (PBPU and PPU) was the major number of claims ($12.5million [30.1%] and ($7.3 million [17.7%]), while beneficiaries of government subsidies (PBI) outsideJava Island, conversely, were under average. ConclusionThere was significant increase in health expenditure associated with DR in Indonesia from 2015 to2019, but decreased in 2020 possibly due to COVID-19 pandemic. Majority of funding was spent totreat severe spectrum of DR and concerned in urban area.